2016
DOI: 10.1186/s40064-016-1871-8
|View full text |Cite
|
Sign up to set email alerts
|

Early atherosclerosis in normotensive patients with autosomal dominant polycystic kidney disease: the relation between epicardial adipose tissue thickness and carotid intima-media thickness

Abstract: Epicardial adipose tissue thickness (EATT) is suggested as a novel marker of subclinical atherosclerosis. Despite increased carotid intima-media thickness (CIMT) in autosomal dominant polycystic kidney disease (ADPKD) patients, the extent of the relationship between CIMT and EATT is unknown. The main purpose of our study was to evaluate the relation between EATT and CIMT in normotensive ADPKD patients with well-preserved renal function. Fifty-five normotensive ADPKD patients with normal renal function and 50 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“… 10 EAT thickness has significant correlations with right common carotid artery elasticity and IMT. 25 In the present study, EAT thickness had significant positive correlations with β, Ep, PWV-β and IMT, negative correlation with AC, and no significant correlation with AI. With high predictive values for CHD, EAT thickness and IMT are crucial for diagnosing and evaluating the therapeutic effects of CHD.…”
Section: Discussionsupporting
confidence: 46%
“… 10 EAT thickness has significant correlations with right common carotid artery elasticity and IMT. 25 In the present study, EAT thickness had significant positive correlations with β, Ep, PWV-β and IMT, negative correlation with AC, and no significant correlation with AI. With high predictive values for CHD, EAT thickness and IMT are crucial for diagnosing and evaluating the therapeutic effects of CHD.…”
Section: Discussionsupporting
confidence: 46%
“…Kocaman et al [15] reported increased atherosclerosis development in early stage ADPKD patients compared to healthy individuals. Sag et al [16] reported that atherosclerosis development as determined by CA-IMT was increased in ADPKD patients compared to healthy individuals. Turkmen et al reported increased atherosclerosis development in ADPKD patients starting from the early stages of CKD [17].…”
Section: Introductionmentioning
confidence: 99%
“…Data on EAT in patients with ADPKD are quite scarce and its relation with LVH was not explored before. However, ultrasound-measured EAT thickness was recently associated with carotid intima-media thickness, a well-accepted marker of subclinical atherosclerosis, in patients with ADPKD [27]. …”
Section: Discussionmentioning
confidence: 99%